Improving the Commercial Practices of an Electrical Utility : Electricity Dispenser System in Tanzania - A Component of the Tanzania Power VI Project - World Bank (Washington, DC, 2012)
The Tanzania Electric Supply Company (TANESCO) has experienced major problems with billing and collecting revenues. To improve customer services; and improve the collection of revenues, the utility company switched to an electricity prepayment system using Electricity Dispensers (ED). The ED which is an electric meter fitted with a circuit breaker, a computer logic chip and an input device, is installed in the customer's premises. The input devices are either magnetic card readers, similar to those on Automated Teller Machine (ATM), or numeric keypads similar to a telephone keypad. The input device allows the customer to control electricity-related consumption and expenditure.